Pembelajaran Menulis Teks Ulasan Film Melalui Optimalisasi Media Film dengan Meggunakan Model Discovery Learning Kelas XI MIPA SMA Negeri 8 Bandung - Damayanti, Tati (Wistara: Jurnal Pendidikan Bahasa dan Sastra, 2020)
The goal of the research is examining: (1) the difference in writing movie reviews between the students who get treatment through optimization of Film Media using the Learning Model of Discovery Learning and the students who use the expository learning model. (2) the difference in learning activities in writing movie text reviews between the students who get treatment through optimization of Film Media using the Learning Model of Discovery Learning and the students use the expository learning model. (3) the correlation between the ability to write movie reviews between the students who get treatment through the optimization of film media using a discovery learning model and the students who use the expository learning model. The research method is The Mix Method type of Embedded Design. The population in this research is the XI grade in State Senior High School 8 Bandung, and the samples is selected randomly (Random sampling), the class XI SCIENCES 6 is made as a controlling class, while the class XI SCIENCES 5 is used as an experiment class. The instruments used in this reseach, are test and non-test instruments. The test instrument is in the form of test writing skills movie reviews and the non-test instrument is in the form of questionnaire and interviews. Based on the results of data analysis and hypothesis testing, it is concluded that: the ability to write movie reviews on students who get treatment through optimization of film media using discovery learning model is better than the students who use the expository model. The activity of the students learning to write movie reviews who get treatment through optimization of film media using model of discovery learning is better than the students who use the expository model. There is no correlation between the ability to write movie reviews on students who get treatment through optimization of film media by using a model of discovery learning is better than the students who use the expository model.